Powering Nation (International Journal of Engineering and Computer Science, 2017)
Powering Nation means developing nation as powerful nation. It depends on energy. Energy is the chief gauge of all of categories work done by human beings and nature. Energy sources are of two genuses there are renewable and non-renewable. Examples of renewable sources are solar, wind, hydropower, tidal hydropower and geothermal energy. These are generally sustainable and environmentally friendly. Non-renewable sources are extracted or created after considerable damage to the environment. Examples are coal, petroleum, natural gas and nuclear power. Geothermal energy is an unimpeded source of energy and is available from earth crust. Maneuver of geothermal energy resource is a swap resource for conventional energy resources. Geothermal energy is a clean energy resource. It not only produces electricity but also has many applications like space heating, drying, industrial processes. In USA and New Zealand the usage of geothermal energy is very high. In India the convention of geothermal energy is in burgeoning juncture.